Impact of background music on reading comprehension: influence of lyrics language and study habits - Sun, Yanping; Sun, Chuanning; Li, Chang; Shao, Xinrui; Liu, Qingming; Liu, Hongen (Frontiers in Psychology, 2024)
Numerous studies have explored the effects of background music on reading comprehension, however, little is known about how native language (L1) lyrics and second language (L2) lyrics in background music influence reading comprehension performance for college students. The present study used a mixed experimental design to examine the effects of listening habits (between-participants variable: non-listeners or listeners), music type (between-participants variable: L1 (Mandarin) pop music, L2 (English) pop music or no music) and text language (within-participants variable: L1 or L2) on reading comprehension of college students in East China. A total of 90 participants (50 females) were screened into non- listeners (n = 45) and listeners (n = 45), and then were randomly assigned to one of three groups: Mandarin pop music group (n = 30), English pop music group (n = 30) and no music group (n = 30). The results showed that reading comprehension performance was negatively affected by music with lyrics compared to the no music condition. Furthermore, Chinese/English reading comprehension was reduced more by pop music in the same language as the written texts. As expected, non-listeners were more negatively affected by music with lyrics than listeners. For both listeners and non-listeners, average reading comprehension accuracy rates were the lowest in the condition of music with native language lyrics. Overall, our research findings indicate that listening to pop music with lyrics reduces reading comprehension performance. However, listening to background music cause much less distraction if the students commonly listen to music while reading. The current study supports the duplex-mechanism account of auditory distraction.